A review: extraction, phytochemicals, and biological activities of rambutan (Nephelium lappaceum L) peel extract. Issue 11 (November 2022) - Tingting, Zhang; Xiuli, Zhou; Kun, Wang; Liping, Sun; Yongliang, Zhuang
Abstract: Rambutan ( Nephelium lappaceum L.) peels are produced during application process. Drying methods of rambutan peel, including open sun, oven, oven vacuum, and freeze-drying, have been describes in this study. The extraction technologies of dried rambutan peels were reviewed, such as maceration and hot extraction, microwave-assisted extraction, ultrasonic-assisted extraction, and supercritical fluid extraction. The phytochemicals of rambutan peel extracts were analyzed, and the purification and stability of geraniin was reviewed. Rambutan peel extracts exhibit wide bioactivities in vitro and in vivo, and these bioactivities depend chiefly on the phenolic contents and profiles in the different extracts. The safety of rambutan peel extracts was analyzed. In addition, rambutan peel extracts could be used as important components to make different products, which are potentially applied in food, medicine, and cosmetic. However, the extracts efficiency must be further increased using some emerging technologies. Furthermore, the bioactive mechanism and bioavailability of the extract in human system should be further evaluated. Abstract : Fruit; Drying methods; Purification; Bioactive compounds; Functional food.